Beneficial Role of Biofertilization on Yield Related Characteristics of Two Apple Cultivars and Soil Microorganisms under Orchard Conditions - Pešaković, Marijana; Tomić Јelena; Lukić, Milan; Karaklajić-Stajić, Žaklina; Miletić, Rade; Paunović, Svetlana M. (European Journal of Sustainable Development, 2017)
Intensive development of agriculture and increasing utilization of synthetic nitrogen fertilizers significantly contributes to a series of undesirable effects and results in excessive environmental pollution. Approximately half of all nitrogen applied to boost agricultural production escapes its intended use and is lost to the environment. Over the past years, fruit growing practice has been focused on a new concept, which relies primarily on the application of microbial inoculants i.e. biofertilizers. In line with the concept, we conducted comparative study of the effect of bio- and chemical fertilizer applications on yield-related characteristics of „Granny Smith? and „?adel? apple cultivars and microbiological properties of the soil. The yield-related characteristics of the tested plants were evaluated for generative potential parameters i.e flowering intensity, fruit set intensity, final fruit set intensity and yield (kg tree-1; t ha-1).The microbiological properties of soil were monitored by determining the total microbial count, numbers of soil fungi, actinomycetes, oligonitrophilic bacteria and Azotobacter. The analysis of the results points to the fact that the efficient apple nutrition management should ensure both enhanced and sustainable production. This approach seems to contain a certain potential as an appropriate technique in commercial apple production, which may improve yield-attributing characteristics and soil fertility. Keywords: bacterial fertilizer, (Malus domestica Borkh), soil biological properties, generative potential